Impacts of long‐term tillage and fertilization on soil carbon stock and aggregate stability in tropical agriculture - Phongsakon Tantarawongsa; Amnat Chidthaisong; Surachet Aramrak; Kazuyuki Yagi; Sudarut Tripetchkul; Patikorn Sriphirom; Wattanai Onsamrarn; Wanida Nobuntou; Wanlee Amornpon (Agricultural & Environmental Letters, 2025)
Abstract This study investigates the effects of tillage and fertilization on the changes of soil organic carbon (SOC) stock in a 46‐year long‐term field experiment in Thailand. The economic cropping system was maize–mung bean rotation. The experiment treatments included plots with tillage, no tillage, chemical fertilizer, organic amendment, and combination of chemical and organic fertilizer. No‐tillage significantly increased soil aggregate stability (water‐stable aggregates [WSA], mean weight diameter, and geometric mean diameter). However, only rice straw applications enhanced WSA. SOC stocks of the same soil mass ranged from 21.7 to 40.1 Mg C ha−1. The highest SOC stock (40.1 Mg C ha−1) and sequestration rate (0.40 Mg C ha−1 year−1) were observed in no‐tillage plots with cow dung and chemical fertilizer. These findings underscore the significant potential of integrated practices involving no‐tillage and organic amendments to improve soil structure and carbon sequestration in tropical agricultural systems. Core Ideas Long‐term tillage practice decreased soil aggregate stability. Crop residue incorporation preserved soil aggregate stability and increased soil organic carbon (SOC) stock. No‐till supplemented with chemical fertilizer and cow dung enhanced SOC stock.